2017
DOI: 10.1002/14651858.cd009422.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E supplementation in people with cystic fibrosis

Abstract: Background People with cystic fibrosis are at an increased risk of fat-soluble vitamin deficiency including vitamin E. Vitamin E deficiency can cause a host of conditions such as haemolytic anaemia, cerebellar ataxia and cognitive di iculties. Vitamin E supplementation is widely recommended in cystic fibrosis and aims to ameliorate this deficiency. This is an updated version of the review. Objectives To determine the e ects of any level of vitamin E supplementation on the frequency of vitamin E deficiency diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 41 publications
0
12
0
1
Order By: Relevance
“…Although doubling the dose of oral vitamin E resulted in increased systemic exposure after 8-week treatment as shown by its plasma concentrations, the lack of antioxidant effect of oral vitamin E 400 UI once daily observed in our study might also reflect a dose which is still insufficient to reach effective antioxidant plasma levels ( Keljo et al, 2000 ). On the other hand, fat-soluble vitamins including vitamin E are routinely supplemented in CF to prevent deficiencies associated with fat malabsorption ( Okebukola et al, 2017 ), whereas their therapeutic use as antioxidants is limited, also in view of the fact that antioxidant doses of vitamin E in CF patients are not established ( Ciofu and Lykkesfeldt, 2014 ) due to the incomplete knowledge of its clinical pharmacology. Although it did not meet the primary outcome of 15% improvement in FEV 1 % of predicted value, a 12-month study showed that treatment with inhaled glutathione improved FEV 1 values over baseline at 3, 6, and 9 months therapy in CF patients with moderate lung disease ( Calabrese et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although doubling the dose of oral vitamin E resulted in increased systemic exposure after 8-week treatment as shown by its plasma concentrations, the lack of antioxidant effect of oral vitamin E 400 UI once daily observed in our study might also reflect a dose which is still insufficient to reach effective antioxidant plasma levels ( Keljo et al, 2000 ). On the other hand, fat-soluble vitamins including vitamin E are routinely supplemented in CF to prevent deficiencies associated with fat malabsorption ( Okebukola et al, 2017 ), whereas their therapeutic use as antioxidants is limited, also in view of the fact that antioxidant doses of vitamin E in CF patients are not established ( Ciofu and Lykkesfeldt, 2014 ) due to the incomplete knowledge of its clinical pharmacology. Although it did not meet the primary outcome of 15% improvement in FEV 1 % of predicted value, a 12-month study showed that treatment with inhaled glutathione improved FEV 1 values over baseline at 3, 6, and 9 months therapy in CF patients with moderate lung disease ( Calabrese et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of a specific vitamin in serum sample below the following reference value was defined as deficiency, vitamin A: 0.70 ”M, vitamin B1: 80.3 nM, vitamin B2: 106 nM, vitamin B6: 20 nM, vitamin B9: 10 nM, vitamin B12: 150 pM, vitamin C: 11 ”M, vitamin D: 50 nM, and vitamin E: 23 ”M. Normal value of serum homocysteine is below 15 ”M [ 24 – 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Genç çocuklarda dĂŒĆŸĂŒk E vitamini dĂŒzeylerinin özellikle beyin fonksiyonlarını etkilediği gösterilmiƟtir (10). ÇalÄ±ĆŸmalar, artmÄ±ĆŸ vitamin E dĂŒzeylerinin kistik fibrozis semptomlarının iyileƟtirilmesinde etkili olabileceğini göstermektedir (13,25).…”
Section: Vitamin Eunclassified